Evaluating ultrastructural preservation quality in banked brain tissue - Garrood, Macy; Keberle, Alicia; Sowa, Allison; Janssen, William; Thorn, Emma; De Sanctis, Claudia; Farrell, Kurt; Crary, John; McKenzie, Andrew (Free Neuropathology, 2025)
The ultrastructural analysis of postmortem brain tissue can provide important insights into cellular architecture and disease-related changes. For example, connectomics studies offer a powerful emerging approach for understanding neural circuit organization. However, electron microscopy (EM) data is difficult to interpret when the preservation quality is imperfect, which is common in brain banking and may render it unsuitable for certain research applications. One common issue is that EM images of postmortem brain tissue can have an expansion of regions that appear to be made up of extracellular space and / or degraded cellular material, which we call ambiguous interstitial zones. In this study, we report a method to assess whether EM images have ambiguous interstitial zone artifacts in a cohort of 10 postmortem brains with samples from each of the cortex and thalamus. Next, in matched samples from the contralateral hemisphere of the same brains, we evaluate the structural preservation quality of light microscopy images, including immunostaining for cytoskeletal proteins. Through this analysis, we show that on light microscopy, cell membrane morphology can be largely maintained, and neurite trajectory visualized over micrometer distances, even in specimens for which there are ambiguous interstitial zone artifacts on EM. Additionally, we demonstrate that synaptic structures can be successfully traced across serial EM sections in some postmortem samples, indicating the potential for connectivity studies in banked human brain tissue when appropriate preservation and visualization protocols are employed. Taken together, our analysis may assist in maximizing the usefulness of donated brain tissue by informing tissue selection and preparation protocols for various research goals.